2009
DOI: 10.1038/cr.2009.140
|View full text |Cite
|
Sign up to set email alerts
|

Quick to remember, slow to forget: rapid recall responses of memory CD8+ T cells

Abstract: The functional roles of memory B and T lymphocytes underlie the phenomenal success of prophylactic vaccinations, which have decreased morbidities and mortalities from infectious diseases globally over the last 50 years. However, it is becoming increasingly appreciated that memory cells are also capable of mediating the pathology associated with autoimmune disorders and transplant rejection, and may pose a significant barrier to future clinical advancement in immunoregulation. Therefore, understanding the uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 65 publications
1
55
1
1
Order By: Relevance
“…Consistent with previous studies (3,4,33), we show here that T M cells are intrinsically different as they proliferate faster and make more cytokine after activation in vitro. This more ready-to-respond state of T M cells has been attributed to several intrinsic differences such as an "open" chromatin conformation of cytokine genes, altered transcription profiles, and enhanced activity of proximal TCR signaling components (1,2). We now show here that rapid proliferation and engagement of glycolysis by T M cells after activation requires mitochondrial ATP to enable optimal HK function.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Consistent with previous studies (3,4,33), we show here that T M cells are intrinsically different as they proliferate faster and make more cytokine after activation in vitro. This more ready-to-respond state of T M cells has been attributed to several intrinsic differences such as an "open" chromatin conformation of cytokine genes, altered transcription profiles, and enhanced activity of proximal TCR signaling components (1,2). We now show here that rapid proliferation and engagement of glycolysis by T M cells after activation requires mitochondrial ATP to enable optimal HK function.…”
Section: Discussionmentioning
confidence: 77%
“…Although quantitative differences in Ag-specific T N and T M cells can contribute to the superior protection conferred by T M cells upon reinfection, studies where equal cell numbers were transferred into mice have shown that these cells respond with distinct kinetics (1,3,5,29,30). T M cells enter the cell cycle earlier and proliferate faster than T N cells after activation (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, memory cells produced all three cytokines (Fig. 4B, treatment 1) as rapid secretion in response to brief stimulation with PMA and IM is their key feature (24,25). Our data suggest differential susceptibilities of these three cytokines to suppression by persistent antigen, probably via stepwise impairment by, or differential recovery from, antigenic exhaustion.…”
Section: Impairment Of Memory Functions By Antigen Persisting Beyond Thementioning
confidence: 71%
“…3A, lower panels), CD3, TCR, CD25, CD69, or the IL7 receptor CD127 (data not shown). Expression of high levels of CD44 on lymphocytes marks cells that are capable of generating rapid functional responses, such as cytokine production, in response to TCR stimulation (24). The changes that confer rapid functional responsiveness in CD44 high cells are primarily at the level of gene transcription, downstream of the TCR signal machinery (25).…”
Section: Increased Number Of Cd8 ϩ T Cells From Dgk-deficient Mice Exmentioning
confidence: 99%